2003
DOI: 10.1002/jnr.10749
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of sesamin and sesamolin on hypoxic neuronal and PC12 cells

Abstract: Reactive oxygen species (ROS) are important mediators of a variety of pathological processes, including inflammation and ischemic injury. The neuroprotective effects of sesame antioxidants, sesamin and sesamolin, against hypoxia or H2O2-induced cell injury were evaluated by cell viability or lactate dehydrogenase (LDH) activity. Sesamin and sesamolin reduced LDH release of PC12 cells under hypoxia or H2O2-stress in a dose-dependent manner. Dichlorofluorescein (DCF)-sensitive ROS production was induced in PC12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 44 publications
8
86
2
Order By: Relevance
“…Cells were also pretreated with isochaihulactone ( Figure 1) or 100 µmol/L α-tocopherol (a potent antioxidant) 3 h before the addition of H 2 O 2 [33] . Pretreatment with isochaihulactone (5 μmol/L or 10 μmol/L) significantly (P<0.05) inhibited this decrease (Figure 2A) 27.6% (10 μmol/L). Pretreatment with 100 μmol/L α-tocopherol also significantly attenuated this increase in LDH release.…”
Section: Isochaihulactone Protected Npc12 Cells Against H 2 O 2 -Indumentioning
confidence: 89%
See 1 more Smart Citation
“…Cells were also pretreated with isochaihulactone ( Figure 1) or 100 µmol/L α-tocopherol (a potent antioxidant) 3 h before the addition of H 2 O 2 [33] . Pretreatment with isochaihulactone (5 μmol/L or 10 μmol/L) significantly (P<0.05) inhibited this decrease (Figure 2A) 27.6% (10 μmol/L). Pretreatment with 100 μmol/L α-tocopherol also significantly attenuated this increase in LDH release.…”
Section: Isochaihulactone Protected Npc12 Cells Against H 2 O 2 -Indumentioning
confidence: 89%
“…Isochaihulactone (also known as K8) is a lignan compound that was identified in acetone extracts of Nan-Chai-Hu and shows antitumor activity against A549 cells in vitro and in vivo [25,26] . Lignan compounds (eg, sesamin, sesamolin) have been reported to act as neuroprotective agents against oxidative injury and excitotoxicity [27][28][29][30] . Lignans can also inhibit lipopolysaccharide-inducible COX-2 expression in macrophages [31] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more researchers have investigated the function of natural compounds. Many studies show a number of products provide antihypoxia action, including sesamin, seasmolin, ginkgolid, and an extract of Curcuma longa L. (Zingiberaceae) (Chen et al, 2001;Hou et al, 2003;Koo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However recent studies suggested several molecular mechanisms for natural antioxidants-mediated neuroprotection against H 2 O 2 intoxication. In fact, these mechanisms were found to be related with activation of the PI3K/Akt and alpha 2-adrenergic signalling pathways, tyrosine kinase of Trk receptors, inhibition of n-methyl-daspartic acid (NMDA) receptors, and regulation of apoptosis (Hou et al 2003;Shin et al 2003;Jiang et al 2003;Liu et al 2010;Iizuka et al 2010;Zhang et al 2012;Vlasova et al 2013).…”
Section: Discussionmentioning
confidence: 99%